2007
DOI: 10.1021/ja071204j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclopropanes via Pd(II/IV)-Catalyzed Reactions of Enynes

Abstract: This report describes a new Pd-catalyzed oxidation reaction for the stereospecific conversion of enynes into cyclopropyl ketones. Unlike related PdII/0, Au, and Pt-catalyzed cyclopropane-forming reactions, these transformations proceed with net inversion of geometry with respect to the starting olefin. This result is consistent with a PdII/IV mechanism in which the key cyclopropane-forming step involves nucleophilic attack of a tethered olefin onto the PdIV−C bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(81 citation statements)
references
References 18 publications
2
76
0
3
Order By: Relevance
“…In two very recent publications, the research groups of Tse [43] and Sanford [44] independantly reported the first examples of oxidative cyclization of 1,6- In view of their versatility as partners in cross-coupling reactions and the multitude of accessible synthetic transformations, attention has been devoted to methodologies that allow the synthesis of complex organometallic reagents. The addition of metal-hydrogen or metal-metal reagents to carbon-carbon multiple bonds represents a well-established approach towards this end.…”
Section: Palladium-catalyzed Oxidative Cycloisomerizationsmentioning
confidence: 99%
“…In two very recent publications, the research groups of Tse [43] and Sanford [44] independantly reported the first examples of oxidative cyclization of 1,6- In view of their versatility as partners in cross-coupling reactions and the multitude of accessible synthetic transformations, attention has been devoted to methodologies that allow the synthesis of complex organometallic reagents. The addition of metal-hydrogen or metal-metal reagents to carbon-carbon multiple bonds represents a well-established approach towards this end.…”
Section: Palladium-catalyzed Oxidative Cycloisomerizationsmentioning
confidence: 99%
“…In zwei kürzlich erschienenen Veröffentlichungen haben die Arbeitsgruppen von Tse [43] und von Sanford [44] [45] Bisher gibt es jedoch nur wenige Anwendungsbeispiele für dieses Konzept auf dem Gebiet der Cycloisomerisierung von 1,n-Eninen.…”
Section: Palladiumkatalysierte Oxidative Cycloisomerisierungenunclassified
“…[2] Recently, a number of palladium-mediated oxidation reactions have been reported that involve Pd IV complexes as key intermediates. [3] Transformations involving these alkyl-palladium(IV) intermediates are particularly attractive because such complexes can readily undergo reductive elimination reactions to form C À O, [4] C À N, [5] C À C, [6] and C À Cl, [7] bonds, which have proven to be difficult to achieve with catalytic Pd II /Pd 0 cycles (Scheme 1). Mechanistic studies of these reactions indicate that the reductive elimination step in most of these reactions occurs in an S N 2-type fashion.…”
mentioning
confidence: 99%